ANALISIS MANAJEMEN STRES GURU DI UPT SMK NEGERI 9 WAJO - Syarmadana; Besse Herlina; Nurcaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of five informants consisting of one principal and four teachers. The results of the study indicate that the factors causing teacher stress include: student misbehavior, inappropriate leadership practices, lack of support, excessive work demands, limited salaries, inadequate facilities and infrastructure, and changes in education policy. The stress management strategies implemented include the development of counseling programs, the implementation of supportive leadership, the building of camaraderie among teachers, the improvement of welfare, the improvement of school facilities, and the effective dissemination of policies. The findings show that even though teachers face various pressures, communicative leadership support from the school, solidarity among colleagues, and professional commitment help reduce stress levels. This study recommends the importance of structured stress management as part of school policy to create a conducive work environment and improve teacher productivity.